STACHYLIDIUM PALLIDUM DEWI SP. NOV. FROM JAVA - Susan Dewi (Research Center for Biology, 2006)
DEWI, N.2006. Stachylidium pallidum sp. nov. from Java. Reinwardtia 12(3): 215–217.––Stachylidium pallidum Dewi sp. nov. is described and illustrated based on a specimen collected from dead leaf of Dendrocalamus giganteus cultivated in Bogor Botanical Garden, West Java, Indonesia.